VISUAL OUTCOME BETWEEN EARLY AND DELAYED VITRECTOMY IN ENDOPHTHALMITIS PATIENTS OPERATED IN KARIADI GENERAL HOSPITAL, SEMARANG : TWO YEARS DESCRIPTIVE STUDY: Oral Presentation - Observational Research - Resident - Rahmayanti, Suci; Pragnanda, Satya Hutama (Ophthalmologica Indonesiana, 2024)
Introduction & ObjectivesEndophthalmitis is a medical emergency caused by infection of tissue or fluids inside the eyeball.Vitrectomy for endophthalmitis is one of the treatment choice and leads to VA gains in some cases.Timing of surgery and visual outcome after surgery are vital to acknowledge. This study aims toanalyze the difference of visual outcome between early and delayed vitrectomy in endophthalmitispatients operated in Dr. Kariadi General HospitalMethodsA Retrospective study held from medical record of patients with endophthalmitis underwentvitrectomy surgery from January 2021 – January 2023 in Dr. Kariadi General Hospital, Semarang.Endophthalmitis patients caused by trauma were excluded. All of the patients had immediatevitrectomy, and based on duration of symptoms, the patients were divided into two groups, earlyvitrectomy (duration of symptoms ? 7 days) and delayed vitrectomy (duration of symptoms > 7days). Independent t- test method was used to analyze the data (significant if p